Achieving electromagnetic wave absorption capabilities by fabrication of flower-like structure NiCo2O4 derived from low-temperature co-precipitation. (November 2022) - Li, Kai; Shen, Yong; Xu, Lihui; Pan, Hong; Shen, Nan; Ling, Hangli; Ni, Kai; Ni, Zhewei; Xiang, Guanghong
Abstract: In this work, The NiCo2 O4 with 3D hierarchical multilayer flower-like structure was prepared by the low-temperature (55 °C) co-precipitation method combined with the calcination process, avoiding the traditional high-temperature hydrothermal synthesis method. The prepared flower-like NiCo2 O4 with a large specific surface area was characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and automatic surface area and porosity analyzer (BET) and vector network analyzer (VNA). A novel evaluation approach was proposed to evaluate the electromagnetic wave (EMW) absorbing properties of various samples (different calcination temperatures), which was to defined the ΔS as the area enclosed by the curve when the reflection loss ( RL ) value was less than −10. In order to take the material thickness into account, and then the effective reflection loss ( RL E ) value was defined ΔS/d to measure the electromagnetic wave (EMW) loss capability of the different samples. The results showed that NiCo2 O4 exhibited excellent EMW absorption effect when the calcination temperature was 400 °C, and the maximum RL value reached −43.17 dB at 14.32 GHz with the thickness of 1.5 mm and the effective absorption bandwidth ( f e ) was 4.48 GHz (12.08 GHz–16.56 GHz). The excellent EMW absorption property was mainly due to NiCo2 O4 with particular porous flower-like structure, which could achieve impedance matching to loss EMW by dielectric loss and magnetic loss. Highlights: The flower-like structure of NiCo2 O4 was prepared by the low-temperature co-precipitation method to achieve the impedance matching effect and obtain an excellent electromagnetic wave absorbing effect. In view of the current lack of a unified scientific evaluation standard in the field of absorbing, this article proposed a more scientific and novel approach for judging the effectiveness of absorbing. According to the unique flower-like structure, a porosity effect was proposed, which was conductive to absorbing the electromagnetic wave by several ways. The preparation process in this article was relatively simple, had low equipment requirements, and could be manufactured in factory.